SGS-LTER live arthropod pitfall trapping across a double catena on the Central Plains Experimental Range, Nunn, Colorado, USA 1995-1998 - Stapp, Paul (Colorado State University. Libraries, 1995)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: invertebrates; population dynamics; arthropods; community dynamics; landscape; catena; populations; animals